Islamic Economics as A New Current of Economic Development in Indonesia - Iskandar Iskandar (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2018)
AbstractThis study explores to provide an alternative solution to the problems of Indonesian economy through the empowerment and embodiment of Indonesia's Islamic economy, by looking at the problems of income distribution, economic inequality and the problem of industrialization. This issue provides a new point of view that Islamic economics is not merely a banking issue. The methodology used in this study is an explanation by describing the phenomena that exist through quantitative and qualitative data. The results of this discussion are expected to provide policy direction for policy makers in solving problems related to industrialization, income distribution and inequality. The main problem of Indonesia's economic development is the lack of wisdom-based development ethics. Lesson in this study is the new current of Islamic economics. Non-usury economic solutions based on wisdom in Islam. Islamic economics has experienced many developments and are increasingly embedded in the hearts of Indonesian muslims. Potency of zakat and waqf endowments, fair income distribution and the process of distribution through the mechanism of production and zakat may render solutions for income disparity and poverty alleviation. AbstrakStudi ini mengeksplorasi untuk memberikan solusi alternatif untuk masalah ekonomi Indonesia melalui pemberdayaan dan perwujudan ekonomi Islam Indonesia, dengan melihat masalah distribusi pendapatan, ketimpangan ekonomi dan masalah industrialisasi. Masalah ini memberikan sudut pandang baru bahwa ekonomi Islam bukan hanya masalah perbankan. Metodologi yang digunakan dalam penelitian ini adalah penjelasan dengan menggambarkan fenomena yang ada melalui data kuantitatif dan kualitatif. Hasil diskusi ini diharapkan dapat memberikan arahan kebijakan bagi para pembuat kebijakan dalam menyelesaikan masalah yang terkait dengan industrialisasi, distribusi pendapatan dan ketidaksetaraan. Masalah utama pembangunan ekonomi Indonesia adalah kurangnya etika pembangunan berbasis kebijaksanaan. Pelajaran dalam penelitian ini adalah arus baru ekonomi Islam. Solusi ekonomi non-riba berdasarkan kebijaksanaan dalam Islam. Ekonomi Islam telah mengalami banyak perkembangan dan semakin tertanam dalam hati umat Islam Indonesia. Potensi zakat dan wakaf wakaf, distribusi pendapatan yang adil dan proses distribusi melalui mekanisme produksi dan zakat dapat memberikan solusi untuk disparitas pendapatan dan pengentasan kemiskinan.